Interventions to Improve Adolescent Nutrition: A Systematic Review and Meta-Analysis - Salam, Rehana A.; Hooda, Mehar; Das, Jai K.; Arshad, Ahmed; Lassi, Zohra S.; Middleton, Philippa; Bhutta, Zulfiqar A. (Journal of adolescent health, 2016)
Adequate adolescent nutrition is an important step for optimal growth and development. In this article, we systematically reviewed published studies till December 2014 to ascertain the effectiveness of interventions to improve adolescent nutrition. We found one existing systematic review on interventions to prevent obesity which we updated and conducted de novo reviews for micronutrient supplementation and nutrition interventions for pregnant adolescents. Our review findings suggest that micronutrient supplementation among adolescents (predominantly females) can significantly decrease anemia prevalence (relative risk [RR]: .69; 95% confidence interval [CI]: .62–.76) while interventions to improve nutritional status among “pregnant adolescents” showed statistically significant improved birth weight (standard mean difference: .25; 95% CI: .08–.41), decreased low birth weight (RR: .70; 95% CI: .57–.84), and preterm birth (RR: .73; 95% CI: .57–.95). Interventions to promote nutrition and prevent obesity had a marginal impact on reducing body mass index (standard mean difference: −.08; 95% CI: −.17 to .01). However, these findings should be interpreted with caution due to significant statistical heterogeneity.